2021
DOI: 10.2196/24733
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Needs Versus Predisposing/Enabling Characteristics in Relation to Internet Cancer Information Seeking Among the US and Chinese Public: Comparative Survey Research

Abstract: Background Since the rise of the internet, online health information seeking has become a worldwide phenomenon. However, health and health communication are inherently culture bound. A data-driven cross-country comparison enables us to better understand how cultural factors moderate the association between individual-level determinants and online health information seeking. Objective The objective of the study was to examine similarities and differences… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…However, the authors also identified resistance to adapting to the new health culture with participants of the study continuing to use health sources hosted in their original culture due to comfort and familiarity. Additionally, another study conducted by Zhang et al (2021) found that immigrants use the internet for health information and that they are more likely to trust family and friends as reliable information sources as compared with U.S. respondents.…”
Section: Health Information Online and Health Behavior Among Minority...mentioning
confidence: 99%
“…However, the authors also identified resistance to adapting to the new health culture with participants of the study continuing to use health sources hosted in their original culture due to comfort and familiarity. Additionally, another study conducted by Zhang et al (2021) found that immigrants use the internet for health information and that they are more likely to trust family and friends as reliable information sources as compared with U.S. respondents.…”
Section: Health Information Online and Health Behavior Among Minority...mentioning
confidence: 99%
“…Similarly, occupational status was re-coded to “currently employed,” with 1 = “Yes” and 0 = “No.” Annual Household Income was originally measured based on the categorical income used in HINTS 2020. A recode into quartiles was considered: “$0-$ 19 999,” “$20 000-$49 999,” “$50 000-$99 999,” and “$100 000 or more.” 19 …”
Section: Methodsmentioning
confidence: 99%
“…A recode into quartiles was considered: "$0-$ 19 999," "$20 000-$49 999," "$50 000-$99 999," and "$100 000 or more." 19 Statistical analysis. Structural equation modeling was used to evaluate the fit of the model, which included the prediction of alcohol consumption measures in physical health (BMI and chronic conditions).…”
Section: Study Variablesmentioning
confidence: 99%